2016
DOI: 10.1186/s12978-016-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of intrapartum stillbirth and associated risk factors in tertiary care setting of Nepal: a case-control study

Abstract: BackgroundEach year, 1.2 million intrapartum stillbirths occur globally. In Nepal, about 50 % of the total number of stillbirths occur during the intrapartum period. An understanding of the risk factors associated with intrapartum stillbirth will facilitate the development of preventative strategies to reduce the associated burden of death. This study was conducted in a tertiary-care setting with the aim to identify risk factors associated with intrapartum stillbirth.MethodsA case–control study was completed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 42 publications
16
36
0
Order By: Relevance
“…The association between pre-eclampsia/eclampsia and stillbirth has been well described in literature as this usually leads to utero—placenta insufficiency, intrauterine growth restriction and consequently intrauterine foetal death. This association has been confirmed in numerous studies [ 14 , 15 , 17 ] and similarly in our study as the odds of developing stillbirth was about 3 times higher in women with a history of pre-eclampsia/eclampsia (OR 2.97, 95% CI 0.87–8.89, p value of 0.03). This association disappeared when we did a multivariate analysis (p = 0.80).…”
Section: Main Textsupporting
confidence: 92%
“…The association between pre-eclampsia/eclampsia and stillbirth has been well described in literature as this usually leads to utero—placenta insufficiency, intrauterine growth restriction and consequently intrauterine foetal death. This association has been confirmed in numerous studies [ 14 , 15 , 17 ] and similarly in our study as the odds of developing stillbirth was about 3 times higher in women with a history of pre-eclampsia/eclampsia (OR 2.97, 95% CI 0.87–8.89, p value of 0.03). This association disappeared when we did a multivariate analysis (p = 0.80).…”
Section: Main Textsupporting
confidence: 92%
“…It has also been corroborated by a meta-analysis which mentioned that women aged 35 years and more contributed to stillbirth (Flenady et al 2011). Similar findings have been reported from other studies (Aminu et al 2014;KC et al 2016;Lawn et al 2016;Yudkin et al 1987).…”
Section: Discussionsupporting
confidence: 80%
“…A recent study conducted in Ethiopia found that women from a wealthy background were less likely to have stillbirths (Lakew et al 2017). Other studies have also found similar linkages for wealth status and stillbirths (Aminu et al 2014;KC et al 2016;Kwagala et al 2016).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Six studies examined the association between prematurity and stillbirth; of which, four case control studies conducted in India [ 17 , 35 ], Bangladesh [ 36 ], and Nepal [ 33 ]; and two cross-sectional studies conducted in India [ 26 ], and Pakistan [ 29 ] found a significant association between premature labour and stillbirth ( Table 1 ). Maternal hypertensive disorder during pregnancy was associated with stillbirth in India [ 17 , 18 ], Pakistan [ 29 ], Nepal [ 32 ], and Bangladesh [ 25 ].…”
Section: Resultsmentioning
confidence: 99%